Ciri-ciri estetika karya Ci Nalan Xingde dan punca pembentukannya - Tan, Poh Wen (2018)
This study is intended to investigate the literary achievement and the graceful stylereflected in Nalans poetry works based on Wong Guoweis literary criticism. Inaddition, the influencing factors that formed the aesthetic features in Nalans poetries are alsothe focus of this study. The methodology of interpretation applied here are Hermeneutics,Aesthetic of Reception and Kants Aesthetics with the aim to correlate the beauty of his poetrieswith the personal background of the poet and the era of Qing Dynasty. The research outcomeindicated that Nalans elegant and euphemistic poetries were greatly influenced by his personal andhistorical background including the family, education and past experience of the poet. Inconclusion, the study has led to the discovery of new characteristics of Ci contributed byNalan on top of the influence by preceding works like Huajian Ci and Liyu. The implication of thisstudy is that the stature of Nalans Ci across the development of China Ci literature isre-evaluated.